2021
DOI: 10.21203/rs.3.rs-729081/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Hybrid Nanocomposite of Imidazolium Based Chitosan and Anderson-type Manganese Polyoxomolybdate for Boosting Drug Delivery Against Breast Cancer

Abstract: Polyoxometalates (POMs) are a class of inorganic cytotoxic agents with potential anticancer effects. As the nano-formulation is one of the best approaches to adjust the therapeutic effects along with selective delivery, in this study, a novel biocompatible nano-composite (NC) of Anderson-type manganese polyoxomolybdate (MnMo6) was prepared using chitosan conjugate to achieve better selective cytotoxicity profile.Imidazolium modified chitosan (CSIm) was utilizedto getthe MnMo6 hybridNCs (MnMo6@CSIm NCs).The bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 58 publications
1
5
0
Order By: Relevance
“…According to the HNMR, the shell signals around 7.5 and 8.7 ppm proved the presence of the imidazolium aromatic features of CSIm. That is in agreement with the previous study [20].…”
Section: Characterization Of Npssupporting
confidence: 95%
See 4 more Smart Citations
“…According to the HNMR, the shell signals around 7.5 and 8.7 ppm proved the presence of the imidazolium aromatic features of CSIm. That is in agreement with the previous study [20].…”
Section: Characterization Of Npssupporting
confidence: 95%
“…Based on the obtained results, POM@CSIm NPs induced RBC hemolysis below 4%, suggesting POM@CSIm NPs for a wide safety margin in blood-contact applications and suitability for intravenous administration. Mahvash et al [20] reported the same results for Anderson-type manganese polyoxomolybdate entrapped in a CSIm shell.…”
Section: Ex Vivo Hemolysis Assaymentioning
confidence: 52%
See 3 more Smart Citations